(untitled) (TAMADDUN NURI JURNALI, 2023)
This article analyzes the historical-philosophical foundations of certain educational approaches in the process of shaping an individual’s spiritual culture. It explores modern interpretations of enlightenment traditions related to the formation of personal consciousness, with a particular focus on the Jadid movement in Turkestan. Special attention is given to the legal, ethical, religious, and cultural dimensions of the issue.